“A Tale of Two Cities:” Boosterism and the Imagination of Community during the Visit of the Prince of Wales to Saint John and Halifax in 1860 - Huskins, Bonnie (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1999)
A phalanx of politicians, newspaper editors, and leading citizens in Saint John and Halifax used the royal visit of 1860 to promote their respective communities to the Prince of Wales and his entourage of British statesmen and reporters. Halifax boosters used the city's status as a provincial capital to impress their international visitors. The Prince and his royal retinue were regaled with a levee, a grand ball, a regatta, numerous military displays, and an excursion to the Prince's Lodge. Organizers in Saint John used a different promotional strategy. They presented their city as a viable commercial centre and insisted that the Prince cross the Reversing Falls Suspension Bridge and ride the European and North American railway line to Shediac. The Prince was also shown how to manufacture deals at a local sawmill. The response to these spectacles was decidedly mixed. While some British and American press correspondents praised the boosters' efforts and the cities themselves, others were quick to ridicule or criticize Halifax and Saint John. Nonetheless, an analysis of the boosters' promotional strategies reveals how they “imagined” their communities to local and international audiences as well as to themselves. Moreover, their efforts illustrate how segments of the urban middle class used this celebration to construct favourable images of their communities to attract international attention and thereby political prestige and economic investment.